WHAT MAKES BRANDS' SOCIAL MEDIA CONTENT SHAREABLE ON INSTAGRAM? A PROJECT TO IDENTIFY NG RADIO INSTAGRAM CONTENT ERROR - Shafa Muthia Annajah; Lina Setiawati (Politeknik Negeri Bengkalis, 2022)
This project aim is to increase brand engagement on NG Radio's Instagram account through analysis of its contents. The types of content used are based on Use and Gratification Theory (UGT). The brand engagement parameters used are the consuming, contributing, and creating stage. The result is NG Radio content error is lack of trial and error so it doesn’t really meet audience need and desire. Informatifve, entertaining, and relational content in the form of Reels Instagram are approved be able to gain brand engagement until contributing stage.Keywords: Brand engagement, Social Media Instagram, Uses and Gratification Theory (UGT)